2012
DOI: 10.21273/horttech.22.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Enhances Student Knowledge Retention in the Plant Sciences

Abstract: Experiential learning can be an important part of an undergraduate curriculum in the sciences. A new course, The Nature of Plants, was developed to provide students across a broad range of majors with an in-depth study of plant science both basic and applied. The course was enriched by using a local natural area as an informal learning environment. We examined whether experiential learning improved homework scores among students who participated in a field trip by asking if simply attending the field t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
2
22
0
4
Order By: Relevance
“…With this question directly involving hydroponic production, an increase was expected as students became more comfortable with hydroponics terminology and maintenance after performing these tasks firsthand over multiple weeks. A similar result was found in research conducted by Bauerle and Park (2012) regarding a tree climbing exercise incorporated into an introductory level plant science course. These authors found that students who performed a hands-on tree climbing exercise scored significantly higher on the related homework assignment than those who did not participate.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…With this question directly involving hydroponic production, an increase was expected as students became more comfortable with hydroponics terminology and maintenance after performing these tasks firsthand over multiple weeks. A similar result was found in research conducted by Bauerle and Park (2012) regarding a tree climbing exercise incorporated into an introductory level plant science course. These authors found that students who performed a hands-on tree climbing exercise scored significantly higher on the related homework assignment than those who did not participate.…”
Section: Resultssupporting
confidence: 83%
“…These authors found that students who performed a hands-on tree climbing exercise scored significantly higher on the related homework assignment than those who did not participate. Overall, students also scored higher on the homework assignment where experiential learning was incorporated compared with assignments where it was not (Bauerle and Park, 2012). Additionally, the LOL index scores significantly increased from Time 1 to 2 and also from Time 2 to 3 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…While a variety of techniques for a course instruction exist, including project-based/experiential learning (Bauerle & Park, 2012;Edwards, Jones, Wapstra, & Richardson, 2012;Nielsen, Du, & Kolmos, 2010), the traditional lecture approach and approaches promulgated in conjunction with various learning technologies, and classroom designs (Beichner et al, 2007;Beichner, Saul, Allain, Deardorff, & Abbott, 2000;Kerlin, 2013), a course is fundamentally constrained by student and administrator expectations related to contact hours Program title Institution and workload (Heffernan, 1973). The Association for Computing Machinery has been providing recommendations regarding the structure, content, and (for master's-level degrees) course progressions for graduate level computer science courses/programs since at least 1968 (Atchison et al, 1968).…”
Section: Coursework and Dissertationmentioning
confidence: 99%
“…They also indicated that they gained an appreciation of the duties of a professional job in the field and assessed themselves as "better prepared" for workforce entry or to pursue graduate studies. Bauerle and Park (2012) conducted work that demonstrated the value of an experiential exercise in increasing knowledge retention. They found that students who participated in the experiential exercise increased homework scores by 12% and the scores of those who fully participated (including participating in a tree climbing exercise) increased by 19%.…”
Section: Experiential Learning For Undergraduatesmentioning
confidence: 99%